Spatial–temporal pattern of urban ecological construction in the Yellow River basin and its optimization and promotion paths - Xiaohui, Wang; Qian, Che; Longsheng, Wang; Guangyu, Li; Haiyan, Sun; Weishan, Qin; Shuang, Chen; Shimou, Yao; Liwei, Meng; Xiaoqian, Yu (Frontiers in Ecology and Evolution, 2023)
Urban ecological instruction is an important method of sustainable development that couples the needs of the population and the environment, thus facilitating high-quality development. This study aimed to transform existing large-scale considerations of ecological urban construction to provide a more grounded evaluation framework. We constructed an integrated framework that considers economic, environmental, social, cultural, and ecological factors and their contribution to urban ecological construction. We used methods of subjective and objective empowerment, exploratory spatial data analysis, and the obstacle degree model to explore spatiotemporal variations in urban ecological construction. Our results showed that: (1) From 2006 to 2018, urban ecological construction in the Yellow River basin (YRB) exhibited a “polycentric” spatial differentiation pattern and a significant, gradually decreasing “center-periphery” spatial distribution trend. (2) High–high areas (with high agglomeration and high urban ecological construction) in the YRB are mainly distributed in Shandong Province and the adjacent regions, whereas low–low areas are mainly distributed in south–central Ningxia Province and southern Gansu Province. (3) Analysis of urban ecological construction characteristics across different city scales, functional types, spatial carriers, and basin locations shows that the urban ecological construction level is directly proportional to the scale of the city. The level of urban ecological construction is relatively higher in the Shandong Peninsula urban agglomeration, in the priority development area of the North China Plain, and in the downstream and right bank of the YRB. Spatial differences are mainly controlled by the net difference between regions from the upstream and midstream scales, as well as intra-regional differences between the left and right banks. (4) Marked differences can be observed in the obstacles to ecological construction in different types of cities. Typical barriers in cities in the YRB include the total water resources per capita, energy consumption per unit of GDP, the proportion of research and development investment in fiscal expenditure, the number of books in public libraries per 10,000 people, and land use efficiency. In the future, urban ecological construction should be based on the development conditions of each individual city, and should be improved according to local conditions to achieve the construction high-quality ecological cities.